Pengarusutamaan Meaningful Learning Melalui Pendidikan Agama Islam Kontekstual - Ichsan, Yazida; Nuryana, Zalik; Hamami, Tasman; Sukiman, Sukiman (Universitas Muhammadiyah Yogyakarta, 2025)
Nowadays, along with the dynamics of the times, education is required to transform the learning process, including Islamic religious education. Sharp criticism of the development of epistemology and learning processes that are less reflective and progressive has caused Islamic religious education to be considered to have no significant impact on developing the potential of students in realizing perfect human beings. Based on these problems, academics conduct discourse and evaluation related to multi-perspective Islamic religious education, one of which is through the medium of implementing contextual Islamic religious education. The study entitled Mainstreaming Meaningful Learning Through Contextual Islamic Religious Education basically aims to describe the concept of meaningful, contextual learning and its actualization in Islamic religious education. This study is a library research conducted by writing, clarifying, reducing and presenting data from various documents. The results of the study indicate that contextual learning as an approach in learning is one of the most important aspects in instilling and actualizing meaningfulness in learning. Through four main characteristics activating knowledge, understanding knowledge, applying knowledge, and reflecting knowledge, students are expected to not only understand knowledge but also implement and reflect on it, ensuring it is appropriate and meaningful. Contextual learning can be implemented in three main domains: first, through contextual learning; second, through the development of contextual Islamic religious education materials; and third, through curriculum development that emphasizes contextual aspects.